Development and validation of food safety and hygiene assessment form and the knowledge and practice of food safety in Kota Bharu Kelantan preschools - Khalid, Mohd Khairul Ashraf (2023)
Introduction: The hygiene of the food preparation areas in preschool is essential to ensuring the food produced is safe to be consumed by the preschool students. This can be achieved by the preschool's teacher having good food safety knowledge and practise. However, the current checklist used in the inspection of the food preparation areas in preschools in Malaysia has not been revised since 2012. Thus, there is a need to improve the content of the checklist to ensure that all relevant parameters are covered during the preschool inspection. Objective: Phase 1 of this study is to develop and validate an observation checklist for assessing the hygiene and sanitation of preschool food preparation areas. Phase 2 aimed to: 1) determine the level of knowledge and practise of food safety among preschool teachers using a validated questionnaire; 2) evaluate the hygiene level of the food preparation area in the preschool using the newly developed and validated checklist in Part 1 of this study; and 3) determine the association between the knowledge and practise of food safety among preschool teachers and the hygiene of food preparation areas in the preschool. Methodology: The study was conducted in Kota Bharu, Kelantan, from April 2021 to February 2022. Phase 1 of the study involved the development and validation of the observation checklist, conducted in four stages: 1) the construction of domains and items from the existing literature; 2) content validation by six experts (using the item-level content validity index [I-CVI] and the scale-level content validity index [S-CVI]); 3) face validation by 10 experts (using the item-level face validity index [I-FVI] and the scale-level face validity index [S-FVI]); and 4) reliability analysis (using the inter-correlation coefficient [ICC]). Four assessors performed the reliability analysis at two preschools. Phase 2 was a cross-sectional study conducted from April 2021 until February 2022. The study involved 70 preschools and 70 preschool teachers in Kota Bharu, Kelantan. This study used a validated questionnaire to determine preschool teachers' food safety knowledge and practises and a validated observation checklist to assess the hygiene of food preparation areas in preschools. Results: Phase 1: The initial draft of the checklist contained three domains and 57 items: 1) building and facility (10 subdomains and 38 items); 2) process control (4 subdomains and 12 items); and 3) food handlers (1 subdomain and 7 items). The I-CVI scores for building and facility, process control, and food handlers were 0.97, 1.00, and 1.00, respectively, indicating good relevancy of items. The S-CVI value was 1.0 for all domains, showing good relevance of the items. The I-FVI above 0.8 and S-FVI above 0.9 for all domains imply that the participants easily understood the checklist. The ICC for the three domains combined was 0.848 (95% CI 0.772–0.904). The final validated checklist consists of 3 domains with 57 items. Phase 2: All of the study participants in this study were female (100%) with an average age above 30 years old (65.7%), and the majority of them completed education at STPM/STPMV/Diploma levels (65.7%). Almost all participants were vaccinated with an anti-typhoid vaccine (97.1%) and underwent food safety training (97.1%). The average mean score for knowledge of food safety and practise of food safety among the study participants was 71.6% (SD = 10.73) and 86.1% (SD = 5.81), respectively. The average mean score for the hygiene of the food preparation areas in preschool was 62.6% (SD = 9.86). Work experience was significantly associated with food safety knowledge among study participants (AdjB 0.411; 95% CI: 0.031–0.612; p = 0.021). Food safety training (AdjB 0.426; 95% CI: 0.021–0.633; p = 0.001) was significantly associated with the practise of food safety among study participants. The hygiene score of the food preparation areas in preschool was significantly associated with work experiences (AOR 1.82; 95% CI: 1.6–2.2; p = 0.012) and secondary education level (AOR 24.50; 95% CI: 1.287–46.774; p = 0.031). Conclusions: The newly developed observation checklist is a valid and reliable tool for assessing the hygiene and sanitation of preschool food preparation areas. The food safety knowledge and practise among preschool teachers were good; however, they failed to translate into good hygiene levels in food preparation areas in preschools. The preschool hygiene level can be improved by regular monitoring by health authorities or administrators and by periodic food safety education and training, primarily focusing on those lacking work experience, never attending food safety training courses, and having low education levels..